Deceptive Marketing Communication and Student Enrollment Decisions in Private Higher Education Institutions (PHEIS) In Cameroon - Joyvice, CHOFOR; Noela Buwah, NEBA; CHOFOR Innocent, LEHTENO (British Journal of Marketing Studies, 2019)
The University Reforms in the early 90s in Cameroon set the stage for private interests, driven by economic gains to invest in the Higher Education Sector.  One of the outcomes of this move is the prevalence of misleading marketing communications that seek to attract and influence university enrollees.  Focusing exclusively on alumni these private university institutions, this paper employs snowball sampling of six hundred subjects and a logistics regression technique to gauge the true influence of deceptive marketing communication on students’ decisions to enroll in PHEIs. The findings reveal that, although 93.5 percent  of  alumni  admit to have been deceived to enroll in their respective alma maters (PHEIs), there is no inferential evidence  that student enrollment decisions are  induced by deceptive marketing communication.